(untitled) (Universa Medicina, 2013)
BACKGROUND Data collected in 2010 from Cipto Mangunkusumo Hospital indicate that complicated skin and soft tissue infections accounted for more than 10% of cases. Etiological diagnoses are based on the findings on bacterial culture and thus evaluation of the effectiveness of bacterial culture becomes a necessity. The purpose of this study was to evaluate the operational effectiveness of bacterial culture for etiological diagnosis of complicated skin and soft tissue infections. METHODS This was a historical cohort study using secondary data of patients with complicated skin and soft tissue infections admitted for hospitalization to Cipto Mangunkusumo Hospital, Jakarta from July 2011 to July 2012. The 90 subjects meeting the inclusion and exclusion criteria were divided into 2 groups of 45 patients each. Group 1 comprised patients who received initial antibiotic therapy according to cultural results, while the patients in group 2 received initial antibiotic therapy without reference to cultural results. Successful diagnostic culture was assessed by the absence of therapeutic failure. Therapeutic failure was determined using 3 parameters that had to be fulfilled, viz. absence of antibiotic escalation, repeat operations, and clinical deterioration. The latter parameter was assessed by clinical judgement of the attending physician. RESULTS After controlling for confounding variables (age, severity of infection, comorbidity), there was no statistical difference in therapeutic success between culture-based and non-culture based initial antibiotic therapies (OR=0.45, p=0.085). CONCLUSION This study demonstrates the ineffectiveness of bacterial culture as a diagnostic criterion for appropriate antibiotic therapy of complicated skin and soft tissue infections.